Realized stable BP-N at ambient pressure by phosphorus doping - Guo Chen; Chengfeng Zhang; Yuanqin Zhu; Bingqing Cao; Jie Zhang; Xianlong Wang (Matter and Radiation at Extremes)
Black-phosphorus-structured nitrogen (BP–N) is an attractive high-energy-density material. However, high-pressure-synthesized BP-N will decompose at low pressure and cannot be quenched to ambient conditions. Finding a method to stabilize it at 0 GPa is of great significance for its practical applications. However, unlike cubic gauche, layered polymeric, and hexagonal layered polymeric nitrogen (cg-N, LP-N, and HLP-N), it is always a metastable phase at high pressures up to 260 GPa, and decomposes into chains at 23 GPa. Here, on the basis of first-principles simulations, we find that P-atom doping can effectively reduce the synthesis pressure of BP-N and maintain its stability at 0 GPa. Uniform distribution of P-atom dopants within BP-N layers helps maintain the structural stability of these layers at 0 GPa, while interlayer electrostatic interaction induced by N–P dipoles enhances dynamic stability by eliminating interlayer slipping. Furthermore, pressure is conducive to enhancing the stability of BP-N and its doped forms by suppressing N-chain dissociation. For a configuration with 12.5% doping concentration, a gravimetric energy density of 8.07 kJ/g can be realized, which is nearly twice that of trinitrotoluene.